Heat transfer improved and turbulent hydrodynamic characteristics: pin-fin heat sinks - N. Bessanane; M. Siameur; M. Rebay; Y. Demagh (University of Eloued, 2023)
Pin-fins are frequently used to improve the heat transfer surface and promote turbulent motion, which improves the device's cooling process by enhancing heat dissipation, as in electronic devices and different cooling systems for industrial applications. The application has a burst out this last decade and became vital in several industrial devices. The present study is a numerical investigation of flow and heat transfer in pin-fin heatsinks (PFHS). The pin-fins have a diamond shape arranged in a segregated disposition (corrugated channel). To adequately calculate the heat transfer coefficient within this complex thermal system; several parameters, such as mass flow rate, geometry dimensions, heat flux and reference temperature are extensively examined. The importance in the way the correct estimation of the heat transfer coefficient led to better optimization of the cooling process performances. This work aimed to elaborate a parametric study to correctly estimate the temperature difference between the cooler fluid and the heat sink wall. For this purpose, a comparative method of 3-D stationary numerical simulations was conducted between laminar and different turbulence models (standard k–, RNG k–, Realizable k–, standard and SST k–), and under turbulent conditions allowing us to compare the characteristic flow effects. We are interested mainly in the determination of the better approach for heat transfer coefficient estimation. An approach with variable reference temperature (VRT) has been adopted in the calculation of the wall-fluid temperature difference. The numerical procedure has been validated by experimental measurements. The proposed methodology to calculate the reference temperature leads to a better presentation of the heat transfer coefficient, in particular the variation of the averaged heat transfer coefficient against Reynolds number. The results obtained show that the model Realizable k– is better because it gives more precise results, which are from the physical point of view and closer to the experimental one
Intervention
Keywords: micro/mini-channels; pin-fin heat sinks; heat transfer enhancement; turbulence; Re effects; CFD